Solid phase data of surface sediments retrieved from two fjords in South Georgia, sub-Antarctica - Berenice Ebner; Susann Henkel; Peter Kraal; Daniel Müller; Male Köster; Michael Staubwasser; Katja Laufer-Meiser; Laura Kattein; Walter Geibert; Sabine Kasten (PANGAEA, 2025)
During the PS133/2 research cruise with the German research vessel RV Polarstern in the austral summer of November and December 2022 into the Southern Ocean, sediment samples were collected using a multicorer at five stations and a handheld gravity corer (UWITEC) from a zodiac at two additional stations across two fjords in South Georgia: King Haakon Bay and Cumberland Bay. The main objective was to determine and quantify the different sources and transport pathways of iron from two fjords of South Georgia into the open ocean. For the determination of an age model and the porosity, at five stations excess 210Pb (210PbXS) was measured using freeze-dried sediment samples. At six stations 0.5 M HCl extractions were performed to determine the 0.5 M HCl-extractable Fe(III)s (bound in poorly crystalline Fe-oxides) and Fe(II)s (bound in acid volatile sulfide). Samples of the same stations were used to obtain sulfate reduction rates (SRR).
In: Ebner, B et al. (2025): Oxygen profiles, pore-water- and solid phase data of surface sediments retrieved from two fjords in South Georgia, sub-Antarctica [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.986658